Structural and chemical characterization of the hardening phase in biodegradable Fe–Mn–Pd maraging steels. Issue 9 (12th May 2014) - Moszner, F.; Gerstl, S.S.A.; Uggowitzer, P.J.; Löffler, J.F.
Abstract: Abstract : Fe–Mn–Pd alloys are promising candidates as biodegradable material for use in temporary implant applications. In this study, the hardening phase of Fe-rich martensitic alloys containing 1, 3, and 6 wt.% Pd and a fixed Mn content of 10 wt.% was investigated. All of these alloys show considerable age-hardening upon isothermal aging at 500 °C, exhibiting a behavior characteristic of maraging steels. Atom probe tomography (APT) and x-ray diffraction (XRD) measurements were performed to characterize the composition and crystallography of nanometer-sized precipitates forming in the overaged region of the Fe–Mn–Pd alloys. The precipitates consist mainly of Mn and Pd and the peaks of the intermetallic particles observed in the XRD spectra can be ascribed to the face-centered tetragonal β1 -MnPd phase. The precipitation sequence for Fe–Mn–Pd is revealed to be similar to that reported for Fe–Mn–Ni and Fe–Mn–Pt maraging steels.